A staff development programme for merged and incorporated South African higher education institutions - Redelinghuys, Jacobus Nicolaas (University of the Free State, 2003)
Mergers and incorporations in higher education institutions are a world-wide phenomenon. The reasons why higher education institutions merge are not different from those of companies in the corporate sector, however, the initiators of the mergers/incorporations differs in the case of higher education institutions, because it is usually the government. When higher education institutions merge/incorporate, these institutions undergo major transformation. This transformation may include changes in the physical environment and resources, the location of the higher education institution, the administrative system of the higher education institution, its support structure, student and staff composition and as well as academic programmes. The South African higher education sector had to transform because it was characterised by fragmentation as a result of the previous political dispensation. The result was that the South African higher education sector consisted of 21 universities, 15 technikons and 96 colleges of education and was characterised by racial and gender inequalities. After the first democratic election of 1994, South African government departments became more integrated and started to function as a coordinated system. The South African higher education system started its transformation process with the establishment of the National Commission on Higher Education (NCHE) by presidential proclamation. The central proposal of the NCHE is that higher education in South Africa must be conceptualised, planned, governed and funded as a single, coordinated system. The change proposed by the NCHE is disruptive and traumatic, especially for people involved in the changing process. When mergers/incorporations occur, the corporations or identified higher education institutions are unaware of the impact of the merger/incorporation on staff. Staff may experience feelings of shock, denial, fear, anger, sadness and blame during the initial phases of the merger/incorporation. Staff may also lose a sense of loyalty towards the institution. This study addresses the problems staff experiences during a merger/incorporation process with a literature review on the history and transformation of South African higher education sector, international experiences of mergers and theoretical perspectives on mergers. It continues by describing how staff perceives a merger. The second stage of the study provides an empirical investigation on how staff perceives mergers/incorporations. The investigation focuses on staff and management, especially the interaction and communication between staff and management regarding the merger/incorporation. It concludes with the development of a staff developmental programme for merged and incorporated South African higher education institutions. One of the main proposals of the programme is the appointment of an independent merger/incorporation facilitator, who would be without bias towards any of the higher education institutions. This programme is also characterised by identifying staff and management needs during a merger/incorporation, for example: • the identification of management and staff needs; • training for management and staff; • psychological services for management and staff to assist with the merger/incorporation; and • addressing cultural diversity from an institutional and staff perspective. The merger/incorporation process is a changing process. In order for the changes to be as painless as possible, the programme proposes that continuous assessment should be built in throughout all the time-frames to ascertain if the merger/incorporation process, especially how the staff component is integrated, is going according to plan. The study concludes with recommendations on how staff should be accommodated through the different stages of the merger/incorporation process. It reiterates the fact that staff is one of, if not the most important, resource of any institution and should be given the attention it deserves.

Samesmeltings en samevoegings van hoëronderwysinstellings kom wêreldwyd voor. Die redes waarom hoëronderwysinstellings saamsmelt, verskil nie wesenlik van die samesmeltings wat in die korporatiewe wêreld plaasvind nie. Die verskil lê egter daarin dat, in die geval van hoëronderwysinstellings, ‘n regering gewoonlik die inisieerder van die samesmelting is. Wanneer hoëronderwysinstellings saamgesmelt/saamgevoeg word, ondergaan hulle geweldige transformasie. Die transformasie wat voorkom tydens samesmeltings of samevoegings sluit in veranderinge van omgewing en hulpbronne, die fisiese ligging van die hoëronderwysinstelling, die administratiewe stelsel wat deur die hoëronderwysinstelling gebruik word, die hoëronderwysinstelling se onderhoudsisteme, studente en personeelsamestelling en akademiese programme. Die Suid-Afrikaanse hoëronderwyssektor was gefragmenteer as gevolg van die vorige politieke bedeling. Die gevolg was dat die Suid-Afrikaanse hoëronderwyssektor bestaan het uit 21 universiteite, 15 technikons en 96 onderwyskolleges. Hierdie instellings was gekenmerk deur ras- en geslagsongelykhede. Na Suid-Afrika se eerste demokratiese verkiesing in 1994 het die verskillende regeringsdepartemente meer geïntegreerd geword. Die Suid-Afrikaanse hoëronderwyssektor het ook begin transformeer met die daarstelling van die Nasionale Kommissie vir Hoër Onderwys (NKH) deur presidentiële proklamasie. Die sentrale voorstel van die NKH is dat hoer Onderwys in Suid-Afrika gekonseptualiseerd, beplan, bestuur en befonds moet word as ‘n enkele gekoördineerde stelsel. Verandering kan traumaties wees, veral as mense betrokke is by die veranderingsproses. Wanneer samesmeltings of samevoegings plaasvind, is die maatskappye of hoëronderwysinstellings gewoonlik onbewus wat die impak van die verandering op hulle mag hê. Personeel kan gevoelens van skok, ontkenning, vrees, woede, hartseer en verwyt ervaar gedurende die eerste fase van die samesmelting of samevoeging. Personeel kan ook dislojaal voel teenoor hul instelling. Hierdie studie fokus op die probleme wat personeel ervaar gedurende ‘n samesmelting of samevoeging van hoëronderwysinstelllings. Dit word gedoen deur ‘n literatuurstudie oor die geskiedenis en transformasie in Suid-Afrika se hoëronderwyssektor, internasionale ervarings rakende samesmeltings, asook teoretiese perspektiewe oor samesmeltings. Verder fokus die studie op hoe personeel dit ervaar wanneer hoëronderwysinstellings saamsmelt. Die tweede fase van die studie behels ‘n empiriese ondersoek na personeel se ervaring van samesmeltings en samevoegings. Die ondersoek fokus op bestuur en personeel en spesifiek op die interaksie en kommunikasie wat daar bestaan tussen bestuur en personeel tydens ‘n hoëronderwyssamesmelting of samevoeging. Die studie sluit af met die ontwikkeling van ‘n personeelontwikkelingsprogram vir saamgesmelte en saamgevoegde Suid-Afrikaanse hoëronderwysinstellings. Een van die hoofvoorstelle van die studie is die aanstelling van ‘n onafhanklike fasiliteerder om vooroordeel uit te skakel wanneer twee of meer hoëronderwysinstellings saamgesmelt of saamgevoeg word. Van die program se kenmerke is ook om bestuur en personeel se behoeftes te bepaal tydens ‘n samesmelting of samevoeging byvoorbeeld: • die identifisering van bestuur en personeelbehoeftes; • bestuur- en personeelopleiding; • die beskikbaarstelling van sielkundige dienste aan bestuur en personeel vir leiding en terapie tydens die samesmelting en samevoeging; en • die aanspreek van kulturele diversifiteit vanuit ‘n institusionele en personeelperspektief. Samesmeltings en samevoegings is ‘n proses van verandering. Hierdie program stel voor dat deurlopende evaluering deel moet wees van ‘n program om te bepaal of die samesmelting of samevoegingsproses, veral t.o.v. personeelintegrasie, volgens plan verloop. Die studie sluit af met aanbevelings oor hoe personeel geakkommodeer moet word gedurende die verskillende fases van die samesmeltings of samevoegingsproses. Die studie beklemtoon die feit dat personeel een van die belangrikste hulpbronne van enige hoëronderwysinstelling is en die aandag moet kry wat dit verdien.
Thesis (Ph.D. (Higher Education Studies and Development))--University of the Free State, 2003
Keywords: Merger; Incorporation; University; Technikon; Higher education; Staff; Transformation; Development; Programme; Psychological; Employees -- Training of -- South Africa; College personnel management -- South Africa; Universities and colleges -- South Africa -- Employees